Age-related gene expression profiles of immature human oocytes. (23rd August 2018) - Smits, M A J; Wong, K M; Mantikou, E; Korver, C M; Jongejan, A; Breit, T M; Goddijn, M; Mastenbroek, S; Repping, S
Abstract: STUDY QUESTION: What is the difference between the gene expression profiles of single human germinal vesicle (GV) oocytes from women of different ages? SUMMARY ANSWER: There were no statistically significant differences in gene expression profiles of human GV oocytes from women of different ages (range: 25–43). WHAT IS KNOWN ALREADY: It is well established that reproductive capacity declines as women age, which is attributed to oocyte quality since this decline is counterbalanced in older women receiving young donor oocytes. Altered gene expression of human oocytes at different stages of development in relation to female age is one of the suggested mechanisms that could explain the decrease in oocyte quality. STUDY DESIGN, SIZE, DURATION: Between 2012 and 2014, 40 human GV oocytes of 40 women were obtained during follicular aspiration as part of routine ICSI treatment. Gene expression profiles of 38 GV oocytes were determined in four different age groups: 25–30, 31–35, 36–38 and 39–43 years of age. PARTICIPANTS/MATERIALS, SETTING, METHODS: GV oocytes were donated for research and frozen between 3.5 and 7.5 h after follicular aspiration. Subsequently, GV oocytes were thawed and prepared for gene expression profile analysis using Agilent microarrays containing 42 000 Human Gene Expression probe-sets. Gene expression profiles were visualized by hierarchical clustering and the top 500 most differing genes were determined by multidimensional scaling (MDS). Transcripts were analysed in a class comparison between the four age groups and for indicators of biological age: antral follicle count (AFC) and the total dosage of FSH needed for ovarian stimulation. Individual transcripts were analysed using linear regression. A false discovery rate <0.05 was considered statistically significant. MAIN RESULTS AND THE ROLE OF CHANCE: Visualization of gene expression profiles of GV oocytes with hierarchal clustering and MDS demonstrated no clear grouping of samples based on female age, AFC or FSH dosage. The gene expression profile of GV oocytes classified in four age groups revealed no significantly differentially expressed genes between the four different age groups. There were also no significantly differentially expressed genes in the linear regression analysis for individual transcripts against age. LARGE SCALE DATA: Not applicable. LIMITATIONS, REASONS FOR CAUTION: Immature (GV) oocytes obtained from ovarian stimulation cycles were used. Findings may therefore differ for oocytes at other developmental stages and for in-vivo matured oocytes under physiological conditions. Due to our relatively large, but still limited study sample (40 GV oocytes), we cannot exclude that there might be smaller age-related gene-expression differences, i.e. due to a lack of power. WIDER IMPLICATIONS OF THE FINDINGS: We did not find an effect of female age on gene expression profiles of individual human GV oocytes. Other studies have suggested that gene-expression profiles are affected in mature oocytes, which might imply that female age affects oocyte maturation. Alternatively, other mechanisms in human oocytes might cause the age-related fertility decline. STUDY FUNDING/COMPETING INTEREST(S): This study received no external funding and there are no competing interests.